TJNPR 2020
DOI: 10.26538/tjnpr/v4i10.9
|View full text |Cite
|
Sign up to set email alerts
|

Aerial Parts of Euphorbia hirta L. in Polar and Non-Polar Solvents: Phytochemical, Antioxidant and Glucose Uptake Studies for Potential Source of Adjunct Drug for Diabetes

Abstract: Euphorbia hirta L. (Euphorbiaceae) is an herbal plant found in countries with tropical and subtropical climates. It contains biologically active components that have pharmacological properties related to progression of oxidative stress and hyperglycemia. In this study, the dried aerial parts of the plant were refluxed using different polar and non-polar solvents such as water, methanol, ethanol, acetone, ethyl acetate, dichloromethane, and hexane. The effect of solvents used during extraction on the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…basis showed that inflammatory and antioxidant activity [ 30 , 49 ]. Euphorbia hirta aerial parts (Fēi Yánɡ Cǎo), the dried aerial parts extracts of E. hirta showed the antioxidant property using DPPH and FRAP assays, and its anti-diabetic activity were evaluated by glucose uptake assay [50] . E. hirta widely distributed in Asia, it has been found for many biological activities which including antioxidant, anti-bacterial, anti-venom, antimalarial and antiviral (e.g., HIV, DANV, HSV activities) [ 41 , 42 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…basis showed that inflammatory and antioxidant activity [ 30 , 49 ]. Euphorbia hirta aerial parts (Fēi Yánɡ Cǎo), the dried aerial parts extracts of E. hirta showed the antioxidant property using DPPH and FRAP assays, and its anti-diabetic activity were evaluated by glucose uptake assay [50] . E. hirta widely distributed in Asia, it has been found for many biological activities which including antioxidant, anti-bacterial, anti-venom, antimalarial and antiviral (e.g., HIV, DANV, HSV activities) [ 41 , 42 , 51 ].…”
Section: Resultsmentioning
confidence: 99%